2021
DOI: 10.3390/microorganisms9030496
|View full text |Cite
|
Sign up to set email alerts
|

Interconnections between the Oral and Gut Microbiomes: Reversal of Microbial Dysbiosis and the Balance between Systemic Health and Disease

Abstract: The human microbiota represents a complex array of microbial species that influence the balance between the health and pathology of their surrounding environment. These microorganisms impart important biological benefits to their host, such as immune regulation and resistance to pathogen colonization. Dysbiosis of microbial communities in the gut and mouth precede many oral and systemic diseases such as cancer, autoimmune-related conditions, and inflammatory states, and can involve the breakdown of innate barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 102 publications
(159 reference statements)
1
30
0
4
Order By: Relevance
“…Recently, Balakrishnan et al reported an ethnicity-specific association in both the gut and oral microbial profiles between African American and European American children although no correlation analysis was conducted between the oral and gut microbiota within each group [ 55 ]. Khor et al proposed two hypotheses to (at least partially) explain how oral bacteria may be transmitted to the lower digestive tract including the hematogenous route and the enteral route [ 56 ]. Given that the oral microbiotas are constantly swallowed along with saliva and delivered to the gut, we hypothesized that the oral microbiota would share a positive association with the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Balakrishnan et al reported an ethnicity-specific association in both the gut and oral microbial profiles between African American and European American children although no correlation analysis was conducted between the oral and gut microbiota within each group [ 55 ]. Khor et al proposed two hypotheses to (at least partially) explain how oral bacteria may be transmitted to the lower digestive tract including the hematogenous route and the enteral route [ 56 ]. Given that the oral microbiotas are constantly swallowed along with saliva and delivered to the gut, we hypothesized that the oral microbiota would share a positive association with the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supported those of Nakajima et al [ 65 ] and Kato et al [ 66 ] who reported that the oral administration of Porphyromonas gingivalis could significantly alter the gut microbiota composition in mice. This apparent interaction between P. gingivalis and the gut microbiota is plausible because P. gingivalis has been shown to be tolerant of a low pH (i.e., as in the stomach environment) and could therefore actively migrate and proliferate from the oral cavity through the intestinal tract [ 56 , 67 ]. Moreover, the oral administration of P. gingivalis in mice was also found to significantly exacerbate endotoxemia while reducing the transcription of genes such as ZO-1 , occludin and Tjp1 tight junction proteins in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…In the oral cavity, nitrite is actively concentrated by salivary glands reaching up to 2 mM after a dietary nitrate load 58 . The Streptococcus genus dominates the majority of oral surfaces 59 . These bacteria produce by-products of fermentation, lactic and acetic acids, that cause a significant decrease in pH level to 5.5 and below.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a chronic inflammatory disease that can lead to non-reversible damage of supportive tissues (cementum, periodontal ligament, and alveolar bone) surrounding the teeth and tooth loss [80,81]. Mechanistically, the increased concentration of pathogenic bacteria (dysbiosis) within the dental plaque activates a massive deleterious immune response [82]. Indeed, the augmented concentration of bacterial lipopolysaccharides (LPS) and other virulence factors stimulate the production of inflammatory mediators and cytokines (e.g., interleukins (ILs), prostaglandin E2 (PGE2) and tumor necrosis factor-alpha (TNF-α)) and promote the release of the matrix metalloproteinases (MMPs) that contribute to the extracellular matrix remodeling and alveolar bone reabsorption by osteoclasts [83].…”
Section: Oral Dysbiosismentioning
confidence: 99%